Interval training - Williams, C.; Graham, D.
Conditioning is the most basic element of any athletic success. Without it, athletic success is the result luck. While luck is appreciated, it does unexpectedly go wherever it wants. Therefore, to achieve athletic success, luck must be removed and replaced with skill and execution. Only then will you be in control of the things you can control, at the time you need to control them. Proper conditioning shall achieve three things. First, is the obvious plus in physical performance late in the game. Second, is that mental functions are quicker and more apt to be correct when not under physical duress. Third, is that most injuries occur as the players fatigue threshold approaches. There should never be a reason for anyone to wonder, if conditioning was a factor. That would suggest a lack of suitable preparation, which should not be allowed! Everyone must participate! For if just one player, for one instant, at a critical time, is not able to keep up, then that team effort shall be lost for always. The Fartlek Running and Training Program was developed by a strength and conditioning coach to address the physical requirements of intervals, which are found in most team athletics. The idea is that by using a training format which parallels the sport, the benefits of the training are realized more quickly. Quite surprisingly, research that is ongoing today, has shown that with little variation, the same training format works for almost all team sports.